ACUTE AIRWAY OBSTRUCTION DUE TO KALA PATHAR (PARAPHENYLENE DIAMINE) POISONING: A CASE REPORT - Akhtar, Sunarays; Ali, Ulfat (Pakistan Armed Forces Medical Journal, 2020)
Kala pathar (Paraphenylenediamine) is a commonly used chemical for hair dyeing in rural areas of Pakistan. It is a highly toxic substance which when ingested, accidentally or intentionally, causes cervicofacial edema and multiple organ failure. Here we present the case of a young female who was brought at Pakistan Air Force Hospital Jacobabad with typical clinical features of Kala pathar poisoning. Emergency tracheostomy was done to relieve the acute airway obstruction followed by symptomatic treatment which led to the full recovery of the patient. A high index of suspicion helped in the management of the case.